Mass incarceration and the school-to-prison pipeline: the intergenerational transmission of criminalization - Emma K. Tynan; Mark R. Warren (International Journal of Adolescence and Youth)
Although the school-to-prison pipeline and mass incarceration arose in the United States at the same time, scholars have addressed them separately. In this article, we show that both systems rose due to an overreliance on policing in society and are justified through shared racist characterizations of Black and Brown people. They apply the same logics of discipline and control and set Black and Brown individuals on a path to prison. We address how the systems reinforce each other. As Black and Brown students are policed in school, they are similarly more likely to face incarceration. Meanwhile, as Black and Brown parents are incarcerated at high rates, their children suffer the consequences and are susceptible to school pushout through exclusionary punishment, and even subsequent incarceration. The twin systems of mass incarceration and the school-to-prison pipeline create an intergenerational transmission of criminalization. We argue that dismantling these systems must be integrated processes.